2004
DOI: 10.1074/jbc.m314286200
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Expression, Function, and Localization of a Novel (Sixth) Isoform of the Human Sarco/Endoplasmic Reticulum Ca2+ATPase 3 Gene

Abstract: Understanding of Ca 2؉ signaling requires the knowledge of proteins involved in this process. Among these proteins are sarco/endoplasmic reticulum Ca 2؉ -ATPases (SERCAs) that pump Ca 2؉ into the endoplasmic reticulum (ER). Recently, the human SERCA3 gene was shown to give rise to five isoforms (SERCA3a-e (h3a-h3e)). Here we demonstrate the existence of an additional new member, termed SERCA3f (h3f). By reverse transcriptase-PCR using monocytic U937 cell RNA, h3f mRNA was found to exclude the antepenultimate e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
70
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 49 publications
(61 reference statements)
0
70
0
Order By: Relevance
“…However, the lack of an inhibitory antibody specific to SERCA3 prevented validation of these data (note that PL/IM430 is highly specific to only human SERCA3). Nonetheless, because of the conserved nature of SERCA3 amino acid sequence among many species (human, mouse, rat, rabbit, dog, chicken, and cow) and because all six human SERCA3 isoforms display lower apparent affinity for Ca 2ϩ (8,37), it is highly likely that SERCA3 pumps also display low apparent Ca 2ϩ affinity in these animal species. Indeed, studies with recombinant rat and rabbit SERCA3 proteins have shown that those enzymes display lower apparent affinity for Ca 2ϩ as expected (15,44).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the lack of an inhibitory antibody specific to SERCA3 prevented validation of these data (note that PL/IM430 is highly specific to only human SERCA3). Nonetheless, because of the conserved nature of SERCA3 amino acid sequence among many species (human, mouse, rat, rabbit, dog, chicken, and cow) and because all six human SERCA3 isoforms display lower apparent affinity for Ca 2ϩ (8,37), it is highly likely that SERCA3 pumps also display low apparent Ca 2ϩ affinity in these animal species. Indeed, studies with recombinant rat and rabbit SERCA3 proteins have shown that those enzymes display lower apparent affinity for Ca 2ϩ as expected (15,44).…”
Section: Discussionmentioning
confidence: 99%
“…1) Recombinant SERCA3a displayed lower apparent affinity for Ca 2ϩ when assayed for Ca 2ϩ -ATPase activity and E-P formation (K 0.5 ϳ1.1 M vs. ϳ0.3 M for SERCA2b) than other SERCA isoforms (34). More recently, with use of recombinant proteins expressed heterologously, it was shown that all six SERCA3 isoforms display similarly lower apparent affinity for Ca 2ϩ (8,37). 2) SERCA3 differed from other isoforms, in that its pH optimum was 7.2-7.4, whereas that for SERCA1 and SERCA2 pumps was 6.8 -7.0.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The methods used for the analysis of the catalytic cycle in steady-state and transient-kinetic conditions have been previously established from studies with SERCA1a mutants (31,32) and used very recently to characterize SERCA2 (33) and SERCA3 isoforms (34,35) as well as Darier disease (SERCA2b) mutants (33). These methods were directly applicable to expressed human SPCA1 enzymes.…”
Section: Methodsmentioning
confidence: 99%
“…These were essentially performed according to published procedures. 23,24 The primers used to amplify mRNA for PMCA1b, PMCA4b, SERCA2b, SERCA3a-to 3c, and InsP3-R1 to -R3 were detailed previously by us. 23,26,27 PCR was performed acording to Martin et al 23 where a touchdown-PCR was performed using 10 cycles with annealing temperature decrements from 65°C to 55°C.…”
mentioning
confidence: 99%